BRI: China’s role in global peace and development - Aasia Khatoon Khattak (The Journal of Humanities & Social Sciences, 2022)
Belt and Road is an international trade interconnectivity Initiative that intersects countries through seaports, roads, corridors, railways, bridges, gas, and oil pipelines etc. In view of U.S., Japan and India, China’s economic influence and rise is rapidly growing particularly through this initiative which is not for peaceful purposes. The initiative is endorsing cooperation, interdependence, and development throughout among the countries of various regions. It is projecting neoliberalism by empowering the economies of the developing countries and boosting their social progress by providing financial assistance for development infrastructures and projects. It is bringing idea of common peace and development. In paper, the descriptive-analytical approach has been used to examines China’s role under the initiative for promoting mutual, development, peace, and interdependence particularly in Singapore Seaport, Strait of Malacca and Kyaukpru Seaport, Myanmar.